Power Analysis – Experiences and Challenges - Helena Bjuremalm (Department for Democracy and Social Development, SIDA, 2006)
Power analysis can help donors understand underlying structural factors impeding poverty reduction as well as incentives and disincentives for pro-poor development. Such analysis may point to i.a. why resources and authority are not transferred to lower levels of government in spite of decentralisation reforms, why women are not allowed to inherit land, and why poor people’s human rights, in particular, tend to be neglected – and what could be done about such expressions of politics of poverty. This way power analysis, which gravitates to political analysis, may complement other types of analyses referred to in Sida’s policy document, Perspectives of the Poor – social and economic analyses, all of which must take cross cutting concerns into account: such as gender equality, democracy and good governance, respect for human rights, and sustainable development, conflict management and security, social development and security, economic growth, global public goods, and HIV/AIDS. Political, economic and social analyses must always use the perspectives of the poor and the rights perspective as their starting points: key parts include participation, openness and transparency, accountability, and equality in dignity and rights.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - power analysis / análise de poder; power / poder

Power, livelihoods and conflict: case studies in political economy analysis for humanitarian action (Humanitarian Policy Group, Overseas Development Institute, 2003)
What can political economy analysis contribute to humanitarian aid interventions? How can agencies undertake such analysis in difficult environments? This chapter introduces the findings of a study (2001-2002) of four cases: Afghanistan, the eastern Democratic Republic of the Congo (DRC), Sierra Leone and the Casamance in Senegal. Political economy analysis is best conducted alongside existing humanitarian operational activities via integration into existing analytical tools.
OCLC: 717007801
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; power / poder